Future of the forest : struggles over land and law in India - Vaidya, Anand P., 1982- (Cornell University Press, 2025)
"Future of the Forest is a historical and ethnographic account of the life of India's 2006 Forest Rights Act. The book follows the law from the movements that pushed for its passage to a North Indian forest village, showing how the law's meaning was shaped through ongoing collective action"-- Provided by publisher.
Keywords: India. -- Scheduled Tribes and Other Traditional Forest Dwellers (Recognition of Forest Rights) Act, 2006.; Forestry -- Law and legislation -- India.; Forest management -- India.; Forest people -- Legal status, laws, etc. -- India.; Forests and forestry -- Social aspects -- India.; Forêts -- Gestion -- Inde.; Forêts -- Aspect social -- Inde.; POLITICAL SCIENCE / Human Rights; Electronic books.